Fluid description of neutral particles in divertor regimes in WEST. Issue 6 (17th May 2018) - Valentinuzzi, M.; Giorgiani, G.; Marandet, Y.; Bufferand, H.; Ciraolo, G.; Tamain, P.; Serre, E.; Ghendrih, Ph.
Abstract : A new neutral fluid code has been developed as a necessary step towards a hybrid fluid/kinetic neutral model, to be used in ITER or DEMO simulations, where part of the divertor will be very collisional for neutrals. The neutral fluid code, which is able to handle complex geometries in view of the coupling to Soledge2D, is tested on plasma backgrounds obtained by Soledge2D‐Eirene in WEST geometry, for different divertor regimes, and is found to be in fair agreement with the kinetic Monte Carlo solver Eirene. The differences are due to the simplifications introduced in the fluid model and to the fact that a fluid description is not fully valid in these cases.